2018
DOI: 10.1371/journal.pone.0204630
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of vascular access stenosis: Blood temperature monitoring with the Twister versus static intra-access pressure ratio

Abstract: BackgroundThe Kidney Disease Outcomes Quality Initiative (KDOQI) guidelines recommend intra-access flow (Qa) measurement as the preferred vascular access surveillance method over static intra-access pressure ratio (SIAPR). Recently, it has become possible to perform Qa measurement during hemodialysis using thermodilution method called blood temperature monitoring (BTM) with the Twister device. The aim of this study was to investigate the correlation between Qa by BTM and SIAPR and to compare the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…10,13,22 However, only two studies using Twister ® in BF measurement have been reported, and the results were not compared with those from DUS. 14,15 Our study showed for the first time that VA BF measured by BTM correlates with the BF measured by DUS. Also, we confirmed that the degree of VA stenosis predicted by the AUC for BTM BF was not inferior to that of DUS.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…10,13,22 However, only two studies using Twister ® in BF measurement have been reported, and the results were not compared with those from DUS. 14,15 Our study showed for the first time that VA BF measured by BTM correlates with the BF measured by DUS. Also, we confirmed that the degree of VA stenosis predicted by the AUC for BTM BF was not inferior to that of DUS.…”
Section: Discussionmentioning
confidence: 60%
“…However, that group found no correlation between BF measured by BTM and BF measured by the static intra-access pressure ratio method. 14 In a 2012 Spanish study, the correlation coefficient between BF measured by BTM and by the Delta-H method was 0.988. 15 Although the precise coefficients vary from study to study, the results of all showed that BTM could be used as a surveillance method to assess for VA stenosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Il BTM, rispetto al Doppler, non ha costi aggiuntivi, non è operatore-dipendente, si può eseguire durante il trattamento emodialitico senza prolungare il tempo di transito del paziente in ospedale e non richiede attrezzature specifiche che non siano già integrate in alcuni monitor di dialisi. Va inoltre segnalato che la procedura di calcolo del ricircolo a linee invertite è oggi facilitata dall'uso del Twister, un device che consente di invertire le linee del paziente senza disconnetterle manualmente (10).…”
Section: Discussioneunclassified